2009
DOI: 10.1105/tpc.109.070557
|View full text |Cite
|
Sign up to set email alerts
|

A Root-Expressed Magnesium Transporter of theMRS2/MGTGene Family inArabidopsis thalianaAllows for Growth in Low-Mg2+ Environments

Abstract: The MRS2/MGT gene family in Arabidopsis thaliana belongs to the superfamily of CorA-MRS2-ALR-type membrane proteins. Proteins of this type are characterized by a GMN tripeptide motif (Gly-Met-Asn) at the end of the first of two C-terminal transmembrane domains and have been characterized as magnesium transporters. Using the recently established mag-fura-2 system allowing direct measurement of Mg 2+ uptake into mitochondria of Saccharomyces cerevisiae, we find that all members of the Arabidopsis family compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
165
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(172 citation statements)
references
References 65 publications
5
165
2
Order By: Relevance
“…Therefore, it is essential for photosynthesis. Recent studies have revealed that several mitochondrial RNA splicing2 (MRS2)/magnesium transport (MGT) proteins, which are structurally homologous to bacterial Co 2+ resistance A (CorA) proteins and ALUMINUM RESISTANCE1 (ALR1), ALR2, and MRS2 in yeast, play an important role in Mg 2+ transport and plant growth under low external Mg 2+ conditions (Gebert et al, 2009;Lenz et al, 2013;Mao et al, 2014). However, it remains largely unknown how plants maintain cellular Mg 2+ homeostasis under high external Mg 2+ conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential for photosynthesis. Recent studies have revealed that several mitochondrial RNA splicing2 (MRS2)/magnesium transport (MGT) proteins, which are structurally homologous to bacterial Co 2+ resistance A (CorA) proteins and ALUMINUM RESISTANCE1 (ALR1), ALR2, and MRS2 in yeast, play an important role in Mg 2+ transport and plant growth under low external Mg 2+ conditions (Gebert et al, 2009;Lenz et al, 2013;Mao et al, 2014). However, it remains largely unknown how plants maintain cellular Mg 2+ homeostasis under high external Mg 2+ conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Mg 2+ ions are transported in plants by proteins of the MRS2/ MGT family (Gebert et al, 2009). qRT-PCR analysis revealed that none of the eight analyzed MRS2/MGT genes showed a significantly and consistently increased expression level in roots of transgenic plants when compared with wild-type controls (see (A) Summary of changes in the concentrations of all analyzed elements in plants grown under different conditions.…”
Section: Expression Of Genes Encoding Proteins Involved In Nutrient Tmentioning
confidence: 99%
“…Members of the MGT family are expressed in a broad range of plant tissues (Li et al, 2001Mao et al, 2008;Chen et al, 2009;Gebert et al, 2009), and the proteins are located to the plasma membrane or in intracellular organelles, including mitochondria, plastid, and tonoplast (Li et al, 2001Drummond et al, 2006;Gebert et al, 2009;Conn et al, 2011), indicating their roles in Mg 2+ transport in and out of the cell and in exchange among the compartments of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to this family as MGT for simplicity unless studies using different terms are discussed. The Mg 2+ transport activities of several MGTs have been characterized in heterologous systems, including bacteria or yeast mutants lacking Mg 2+ transport capacity (Schock et al, 2000;Li et al, 2001Li et al, , 2008Mao et al, 2008;Chen et al, 2009;Gebert et al, 2009). In these systems, members of the MGT family vary in their affinities for Mg 2+ transport, including highaffinity (MGT1 and MGT10), low-affinity (MGT7 and MGT9), and dual-affinity (MGT5) members (Schock et al, 2000;Li et al, 2001Li et al, , 2008Drummond et al, 2006;Mao et al, 2008;Chen et al, 2009;Gebert et al, 2009).…”
Section: Introductionmentioning
confidence: 99%